Conservative treatment of apical granuloma. Clinical case (Эндодонтия Today)
Today an increasing number of patients apply to the clinic for the treatment and saving the teeth. Possibility of conservative treatment of complicated forms of caries appeared on clinical admission relatively recently thanks to new techniques, as well as tools and materials in endodontics. Stages of treatment, its distinct algorithm, the correct application of various tools in the treatment of root canals - all this significantly affects the outcome of treatment. The purpose of the clinical case - to show the correct application of new techniques during the repeated endodontic treatment. Authors’ experience indicates positive immediate outcomes of repeated endodontic treatment.